Diagnosis Coding for Clinicians: Core Knowledge and Transition to ICD-10 - Davoren Chick; Margie Andreae (Association of American Medical Colleges, 2014)
Abstract Introduction Graduate medical education programs and academic health systems have long struggled with providing sufficient training in the regulatory and business aspects of health care. Needs assessments confirm that medical students, medical residents, surgical residents, and faculty all rank the topic of billing and coding as an area of curricular need. Indeed, data demonstrates that incorrect coding by academic medical center learners leads to large financial losses and that educational content is needed to address the financial needs of academic institutions. Nationally, internal medicine curricular milestones have recognized the understanding of coding and reimbursement principles as a curricular milestone toward development of competence in systems-based practice. Superimposed upon these chronic concerns, the national transition to ICD-10 coding increases the need for immediately available teaching content on the importance of diagnosis coding. Methods In response, Diagnosis Coding for Clinicians: Core Knowledge and Transition to ICD-10 provides succinct educational content that can be individually reviewed by graduate medical and continuing medical learners. The content is specifically designed to assist training programs and learners with the transition to ICD-10 coding in a manner that supports accurate and specific medical coding practices. The content is provided as an interactive audiovisual presentation that automatically launches on standard personal computers or handheld devices. The presentation can be loaded on learning management systems or provided on a training website. An accompanying examination may be used to document minimum knowledge achievement for inclusion in a learning portfolio. Results Diagnosis Coding for Clinicians: Core Knowledge and Transition to ICD-10 is now mandatory for all billing physicians, house officers, and midlevel providers at the University of Michigan Health System, where each mandated learner must pass a content exam with a minimum 80% correct score. Discussion The content has been peer-reviewed and approved by a series of physician leaders, hospital executives, and coding specialists at the University of Michigan Health System. Focus groups of learners have found the information clear, relevant, appropriately succinct, and engaging.